Find the Hidden Object. Understanding Play in Psychological Assessments - Fasulo, Alessandra; Shukla, Janhavi; Bennett, Stephanie (Frontiers in Psychology, 2017)
Standardized psychological assessments are extensively used by practitioners to determine rate and level of development in different domains of ability in both typical and atypical children. The younger the children, the more likely the trials will resemble play activities. However, the mode of administration, the timing, and the use of the objects involved are constrained. The purpose of this study is to explore what kind of play is play in psychological assessments, what are the expectations about children’s performance and what are the abilities supporting the test activities. Conversation Analysis (CA) was applied to the videorecording of an interaction between a child and a practitioner during the administration of the Bayley Scale of Infant and Toddler Development, III edition. The analysis focuses on a 2’07’’ long sequence relative to the administration of the test item ‘Find the hidden object’. The professional is a psychologists; the child has Down syndrome and is 23 months old. The analysis of the sequence shows that the assessor promotes the child’s engagement by couching in communication with marked child-directed features the actions required to administer the item. The analysis also shows that the objects constituting the test item did not suggest to the child a unique course of action, so that the assessor engages in modeling the successful sequence for the child. We argue that when a play frame is activated by an interactional partner, the relational aspect of the activity is foregrounded and the co-player become a source of cues for ways in which play can develop. We discuss the assessment interaction as orienting the child toward a right-or-wrong interpretation, leaving the realm of play, which is inherently exploratory and inventive, to enter that of instructional activities. Finally, we argue that sequential analyses of the interaction and of the mutual sense-making procedures that partners put in place during the administration of an assessment could be used in the design and evaluation of test for a finer understanding of the abilities involved.